Tuning the Crystal Structure and Luminescence of Pyrrolidinium Manganese Halides via Halide Ions. Issue 3 (21st January 2019) - Jiang, Chunli; Fu, Hanmei; Han, Ying; Li, Dong; Lin, Hechun; Li, Bo; Meng, Xiangjian; Peng, Hui; Chu, Junhao
Abstract: Luminescent and lead‐free organic‐transition metal halides (OTMHs) are greatly interesting for optical applications. In this work, six single crystals of pyrrolidinium manganese halides are prepared (C4 H10 N)MnCl3 (1 ), (C4 H10 N)8 (Mn2 Cl10 )(MnCl4 ) (2 ), (C4 H10 N)MnBr3 (3 ), (C4 H10 N)2 MnBr4 (4 ), and (C4 H10 N)2 MnI4 (5 and6 with two different crystal configurations). The analysis of crystal structures illustrates that halide ions play an important role in the crystal structure and further affect the luminescent properties of pyrrolidinium manganese halides. It is only for Cl − and Br − that produce perovskite‐type crystals which exhibit red emission. Other crystals with MnX4 2− tetrahedron unit emit green or yellow lights. It is interesting that the obtained crystals only contain one kind of halide ion with higher atomic number if there are two kinds of halide ions existing in the crystal growth solution. This study illustrates that the luminescent properties of OTMHs can be tuned by halide ions through deliberately designing experiments. Abstract : The luminescent single crystals of pyrrolidinium manganese halides are grown in solution . The analysis of crystal structures shows that halide ions greatly affect the crystal structures which determine the luminescent properties of crystals. Thus, the emission of pyrrolidinium manganese halide crystals can be tuned from green to red by altering halide ions.